PENGARUH EKSTRAK BUAH MENGKUDU (MORINDA CITRIFOLIA) TERHADAP PERTUMBUHAN STAPHYLOCOCCUS AUREUS The Effect of Noni Fruit Extracts (Morinda Citrifolia) on Staphylococcus aureus growth - RISNAYANTI R DJURAMANG; YULIANA RETNOWATI; NURHAYATI BIALANGI (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2017)
This aim of study was to determine the effect of noni fruit extract on Staphylococcus aureus growth. Indicator is the Bacteria growth of diameter inhibitory zone formed. The study was conducted at the Laboratory of Microbiology, Departement of Biology, State University of Gorontalo. The research method was experimental which consisted of 12 treatments (15%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%) and 2 replicates, and quantitatively analyzed using non-parametric Kruskal Wallis Test. Based on the statistical results indicate that there is influence of noni fruit extract on the growth of Staphylococcus aureus at 15%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, and 50% concentrations, with a diameter of inhibition zone formed by each is 7,87mm, 7,75mm, 8,81mm, 9,62mm, 9mm, 10,44mm, 10,88mm, 12mm, 8,37mm and 12,13mm. This result is evidenced by the Kruskal Wallis 000 ≤ 0,05.Keyword: Growth, Staphylococcus aureus,Extraction, Noni, Inhibitory zones